My dog's a mommy! - Bennett, Leonie (New York : Bearport Pub., 2006)
Simple text and photographs describe how Molly takes care of her ten tiny puppies.
My dog Molly -- Going to the vet -- My dog's a mommy -- Ten puppies -- The new puppies -- Growing up -- Time for dinner -- Playful puppies -- Saying good-bye.
Includes bibliographical references (p. 24) and index.
Library Media Connection.
1.9
K-3
Keywords: Puppies -- Juvenile literature; Animals -- Infancy; Dogs; Animal babies; Dogs